ORGANIZATION OF FINANCIAL RELATIONS IN THE ECONOMY - Tatiana P. Nikolaeva (Статистика и экономика, 2016)
The article describes the organization of financial relations in the economy. The main attention is paid to the role of the government in the financial relations regulation with the aim to reduce the economic threat. Russia financial policy is described and the financial market situation is characterized. The author determines the ways of their improvement and development.